Transdisciplinary Problem Solving: A new Approach for Validating Existing Literature - Schneider, Tamás (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2020)
The goal of this study is to present a model to validate pieces of literature in social studies that rely on the concept of transdisciplinarity. The study aims to answer the following question: how can researchers and practitioners validate existing transdisciplinary literature in social studies in an efficient and effective way? The method used in this paper is to build a conceptual model in a knowledge-based system (KBS), which is based on then if-then rules between the values of the attributes identified during the knowledge acquisition process. The model is first introduced and then it is applied to a set of papers incorporating transdisciplinarity in social studies. It is shown that with the help of the model, it is possible to efficiently and effectively validate the group of sample articles and assess their value in a potential transdisciplinary research project.Keywords: transdisciplinarity, knowledge-based system, problem solving